Mengurangi Risiko Low Back Pain (LBP) Pada Lansia Melalui Edukasi Kesehatan Di Gereja Paroki Sant Antonius Purbayan, Surakarta - Aji, Sulistyani Prabu; Syarifah, Syarifah; Putri, Noviyati Rahardjo (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Musculoskeletal disorders are common problems often experienced by the elderly. As we age, musculoskeletal tissue shows increased bone fragility, loss of muscle strength and redistribution of fat to reduce the ability of the tissue to perform its normal functions. One example of a musculoskeletal disorder that is often suffered by the elderly is low back pain (LBP). Health education related to LBP for the elderly is an important first step in preventing and managing low back pain in the elderly. Objectives To increase knowledge in the elderly at the Sant Antonius Purbayan Surakarta Parish Church regarding reducing the risk of LBP in the elderly at the Sant Antonius Purbayan Surakarta Parish Church through a health education program that is implemented. This Community Service activity was held on May 7, 2025 at the Aula Village of the Sant Antonius Purbayan Parish Church, Surakarta. This activity was attended by 101 elderly people. The methods used in this activity were leaflet distribution, direct demonstrations and counseling. The distribution of leaflets aims to provide written information that is easy to read and understand by the elderly, regarding ways to prevent LBP and important information related to back health. In addition, live demonstrations are carried out that allow participants to see firsthand the correct techniques or movements, such as good posture when sitting, standing, or lifting objects, which can reduce the risk of LBP. Finally, counseling is carried out to explain in depth the causes, symptoms, and ways to prevent LBP, with an interactive approach that provides an opportunity for the elderly to ask questions and discuss the health problems they experience. Educational activities about Low Back Pain have proven effective in increasing the knowledge and awareness of the elderly regarding the prevention and reduction of LBP from 53% to 73%.